The evolution of China's banking system: bank loan announcements 1996–2009. (10th July 2012) - Gan, Christopher; Zhang, Yuan; Li, Zhaohua; Cohen, David A.
Abstract This study investigates China's evolving banking systems from 1996 to 2009 by testing the market response to bank loan announcements in the China. The results show a significant negative market response to bank loan announcements in the Chinese financial market for the sample period 1996–2004. However, after a series of reforms in the Chinese banking system, the significantly negative market response to bank loan announcements disappears for the sample period 2005–2009.